2020
DOI: 10.1177/2280800020934652
|View full text |Cite
|
Sign up to set email alerts
|

The integration of pore size and porosity distribution on Ti-6A1-4V scaffolds by 3D printing in the modulation of osteo-differentation

Abstract: Purpose: In this study, pore size and porosity distribution of porous Ti-6Al-4V scaffolds (pTi) were controlled by 3D printing. The effects of pore size distribution at a constant porosity, or porosity distribution at a constant pore size pertaining to functions of adhesion, proliferation, and differentiation of the mouse embryonic osteoblast precursor (MC3T3-E1) cells were researched separately. Methods: 3D printing was used to design five groups of pTi, designated as PS300/HP, PS300/LP, PS500/HP, PS500/LP, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, very small HA particles might induce cytotoxicity if they have been ingested by cells (Epple, 2018). Another previous study has also confirmed the beneficial effects of the pore size and porosity of 3D-printed scaffolds on cell proliferation and differentiation (Wo et al, 2020). However, it is not well understood whether EDHA and PSHA coatings on the 3D printing Ti scaffold can change the aperture and porosity of the scaffold and if there are different effects of these 2 HA coatings on cell proliferation, osteogenic differentiation, and bone integration in vivo.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, very small HA particles might induce cytotoxicity if they have been ingested by cells (Epple, 2018). Another previous study has also confirmed the beneficial effects of the pore size and porosity of 3D-printed scaffolds on cell proliferation and differentiation (Wo et al, 2020). However, it is not well understood whether EDHA and PSHA coatings on the 3D printing Ti scaffold can change the aperture and porosity of the scaffold and if there are different effects of these 2 HA coatings on cell proliferation, osteogenic differentiation, and bone integration in vivo.…”
Section: Introductionmentioning
confidence: 68%
“…However, unlike plain HA coatings, 3D-printed Ti scaffolds have inherent porous structures. Thus, the influence of pore size and porosity of HA coatings on 3D-printed Ti scaffolds should be considered, which may further influence osteointegration ( Wo et al, 2020 ). Hence, various techniques involving the fabrication of 3D-printed Ti scaffolds with HA coating have received increased biomedical research attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…(3) A wide range of available materials: unlike conventional fabricating techniques, 3D printing uses a variety of materials, including metals, alloys, polymers, and bioceramics ( Tardajos et al, 2018 ). (4) Precise individual customization: through a CAD software monitor, the pore size and porosity are made highly consistent with expectations, consequently, it is possible to fabricate gradient scaffolds with accurately designed pore sizes ( Wo et al, 2020 ).…”
Section: Cartilage Tissue Engineering For Gp Injuriesmentioning
confidence: 99%
“…In addition, another crucial aspect that significantly influences the success of bone grafts in producing fracture repair is their structure, especially the adequate size and interconnectivity of the pores, which allow cell attachment, proliferation and differentiation. [14][15][16] In this context, additive manufacturing, also known as 3D printing, has emerged as a disruptive technology for rapid prototyping and for manufacturing bone grafts. 17 3D printing bone grafts have many advantages over other manufacturing techniques, such as the possibility of facilitating potential patient-specific graft fabrication and controlling porosity, introducing interconnected pore structures and managing shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another crucial aspect that significantly influences the success of bone grafts in producing fracture repair is their structure, especially the adequate size and interconnectivity of the pores, which allow cell attachment, proliferation and differentiation 14–16 . In this context, additive manufacturing, also known as 3D printing, has emerged as a disruptive technology for rapid prototyping and for manufacturing bone grafts 17 .…”
Section: Introductionmentioning
confidence: 99%